The Breakthrough Listen Initiative and the Future of the Search for Intelligent Life - Enriquez, J.; Siemion, A.; Falcke, H.; Croft, S.; DeBoer, D.; Gajjar, V.; Hickish, J.; Isaacson, H.; Lebofsky, M.; MacMahon, D.; Price, D.; Tellis, N.; et al. (2017)
No Abstract Available